Aldehyde disinfectants and health in endoscopy unit: The report of a working party of the British Society of Gastroenterology Endoscopy Committee. Issue 11 (November 1993) - Cowan, R E; Manning, A P; Ayliffe, G A J; Axon, A T R; Causton, J S; Cripps, N F; Hall, R; Hanson, P J V; Harrison, J; Leicester, R J; Neumann, C; Wicks, J
Abstract : Summary of main recommendations (1) Glutaraldehyde, used in most endoscopy units in the United Kingdom for the disinfection of flexible gastrointestinal endoscopes, is a toxic substance being an irritant and a sensitiser; symptoms associated with glutaraldehyde exposure are common among staff working in endoscopy units. (2) The Control of Substances Hazardous to Health Regulations 1988 (COSHH) obliges the employer to make a systematic assessment of risk to staff of exposure to glutaraldehyde and institute measures to deal effectively with exposure. (3) At present glutaraldehyde remains the first line agent for the disinfection of flexible gastrointestinal endoscopes. Other agents are being developed; a standard means of assessment for flexible endoscope disinfectants should be devised. (4) Equipment and accessories that are heat stable should be sterilised by autoclaving; disposable accessories should be used wherever possible. (5) Flexible gastrointestinal endoscopes should be disinfected within automated washer/disinfectors; trays, bowls or buckets for this purpose are unacceptable. (6) Local exhaust ventilation must be used to control glutaraldehyde vapour. Extracted air may be discharged direct to the atmosphere or passed over special absorbent filters and recirculated. Such control measures must be regularly tested and records retained. (7) Endoscope cleaning and disinfection should be carried out in a room dedicated to the purpose, equipped with control measures to maintain the concentration of glutaraldehyde vapour at a level certainly below the current occupational exposure standard of 0·2 ppm and preferably below the commonly used working limit of 0·1 ppm. Sites other than the endoscopy unit where endoscopy is regularly performed, such as the radiology department, should have their own fully equipped cleaning and disinfection room. (8) COSHH limits the use of personal protective equipment to those situations where other measures cannot adequately control exposure. Such equipment includes nitrile rubber gloves, apron, chemical grade eye protection, and respiratory protective equipment for organic vapours. (9) Monitoring of atmospheric levels of glutaraldehyde should be performed by a competent person such as an occupational hygienist; the currently preferred method of sampling uses a filtration technique, the commercially available meters being less reliable. (10) Health surveillance of staff is mandatory; occupational health records must be retained for 30 years. (11) Endoscopy staff must be informed of the risks of exposure to glutaraldehyde and trained in safe methods of its control. Only staff who have completed such an education and training programme should be allowed to disinfect endoscopes. (12) The unsafe use of glutaraldehyde has significant health and legal consequences; the safe use of glutaraldehyde may have revenue consequences that contribute significantly to the cost of gastrointestinal endoscopy.